The Experience of Mother in Breastfeeding and Weaning Practice for Baby Under Two Years Old: A Qualitative Descriptive Study - Shinta Widiastuty Anggerainy; Mohamad Ikhsan; Siti Nurul Huda (JURNAL KEPERAWATAN RAFLESIA, 2023)
The experience of Mother in the form of knowledge and skills influences mothers in the practice of feeding their children, both breastfeeding and complementary food as well as weaning practices in baby under two years old. This qualitative descriptive study aims to explore the experiences of mothers in the practice of breastfeeding, complementary food and weaning of baby under two years old. Data was collected from April to June 2022 in Sungai Ana Village and Baning Kota Village, Sintang District. In this study, a sample of ten mothers was conducted in-depth interviews. The results of the interviews were analyzed using the content analysis method. There were 4 themes, namely: 1) Combination of Traditional, Belief, and Modern, 2) Mother: "Breastfeeding Warrior", 3) Mother's Dilemma, and 4) Stages of Feeding Baby. Families, especially mothers have an important role in fulfilling nutrition in baby under two years old. The health professionals should assess the family regarding feeding and weaning practices. Furthermore, the health professionals need to provide information to parents in the form of re-education and training on how to feed children to increase knowledge and develop competence in the quality of feeding and weaning practices in baby under two years old.